Improving students' learning achievement in school musical ensemble through portfolio-based assessment - Kun S Astuti (JOURNAL OF EDUCATION, 2008)
Abstract: In light of the implementation of the competency-based curriculum (CRC), the study aimed to (1) develop portfolio-based  assessment for  the School Musical Ensemble course and (2) find out its impact on the students' learning achievement. The subjects of the study were students of the Department of Music Education at the YogyakartaState University (YSU) who took the Advanced School Musical Ensemble class. Observation sheets were used to collect descriptive qualitative data and students' semester scores were used as datafor the descriptive quantitative analyses. Thefindings of the study indicated that  (1)  classification of students'  learning achievement  in the cognitive, psychomotor, and affective aspects can be used as components of portfolio assessment in musical ensemble and (2) based on the t-test analysis results, there is a significant difference in students' learning achievement before and after the implementation ofportfolio assessment.Key words:competency-based curriculum, education-unit level curriculum, portfolio assessment, authentic assessment, standard of competencies, cognitive domain, psychomotor domain, affective domain, attitudes towards learning